An Autoethnographic Account of Familial Mediterranean Fever: A Turkish Patient's Discovery of Spiritual Meaning - Yuksel, Cigdem (Journal of religion and health, 2025)
Familial Mediterranean Fever (FMF) is a genetic autoinflammatory disorder characterized by recurrent febrile episodes that are accompanied by pain in the abdomen, chest, or joints caused by peritonitis, pleuritis, skin lesions, arthritis, and pericarditis. This original article aims to provide an analytic autoethnographic account of a Turkish patient's experience of FMF, with a focus on the discovery of spiritual meaning. In addition to discussing the grief reactions to a loss of health, the article uses self-reflexive discourse and narrative-based analysis to explore four stages of discovery of spiritual meaning through FMF: "omnipotent me," "God's punishment," "God's test," and "God's mercy." The article provides an in-depth look at the experience of FMF, a chronic and lifelong disease, through a spiritual lens and offers suggestions for mental health professionals and rheumatologists providing holistic treatment to FMF patients that might improve treatment adherence.